Pengaruh Keberadaan Bandara Internasional Jawa Barat (BIJB) Kertajati terhadap Ekonomi Makro Kabupaten Majalengka - Muhammad Abdillah Azis; Nia Kurniasari (UNISBA Press, 2023)
Abstract. The presence of West Java International Airport (BIJB) Kertajati is expected to have a significant impact on the economy of Majalengka Regency in particular and West Java Province in general. Economic driving infrastructure such as the airport is a new hope for the people of Majalengka Regency as a new growth center and new economic potential. BIJB Kertajati has several problems that have reduced the interest of visitors to come to BIJB Kertajati as the main choice of airport. The methodology used in this study is a primary survey such as field observations, interviews and documentation, while a secondary survey through institutional surveys, journal reviews and related literacy. The economic impact of Majalengka Regency with the presence of BIJB Kertajati needs to be further studied by identifying demographic data (population and workforce projections) of Majalengka Regency, regional economic data (GRDP, PAD, APBD), economic potential, economic vulnerability, prospects for economic development (PDRB projections ) Majalengka Regency in the future. The conclusion that was obtained, the presence of BIJB Kertajati had various impacts on the regional economy such as a shift in the economic structure of Majalengka Regency from the dominant agricultural sector to the processing industry sector during the post-development of BIJB Kertajati. Even though at this time BIJB Kertajati has not had a significant economic impact, BIJB Kertajati is projected to have an impact on the economy of Majalengka Regency in the next 20 years. Prospects for economic development can also take advantage of the realization of Kertajati Aerocity and the emergence of new industries around the BIJB area so as to create new jobs. Abstrak. Kehadiran Bandara Internasional Jawa Barat (BIJB) Kertajati diharapkan memberikan dampak yang signifikan untuk perekonomian Kabupaten Majalengka pada khususnya dan Provinsi Jawa Barat pada umumnya. Infrastruktur pendorong perekonomian seperti Bandara menjadi harapan baru bagi masyarakat Kabupaten Majalengka sebagai pusat pertumbuhan baru dan potensi perekonomian baru. BIJB Kertajati memiliki beberapa permasalahan yang menyebabkan berkurangnya minat pengunjung untuk datang ke BIJB Kertajati sebagai pilihan utama bandara. Metodologi yang digunakan dalam penelitian ini yaitu survey primer seperti observasi lapangan, wawancara dan dokumentasi, sedangkan survey sekunder melalui survey instansional, review jurnal dan literasi terkait. Dampak perekonomian Kabupaten Majalengka dengan hadirnya BIJB Kertajati perlu dilakukan pengkajian lebih lanjut dengan mengidentifikasi data kependudukan (proyeksi penduduk dan angkatan kerja) Kabupaten Majalengka, data perekonomian wilayah (PDRB,PAD,APBD), potensi perekonomian, kerentanan ekonomi, prospek perkembangan perekonomian (proyeksi PDRB) Kabupaten Majalengka di masa yang akan datang. Kesimpulan yang didapatkan, hadirnya BIJB Kertajati memberi dampak beragam terhadap perekonomian wilayah seperti pergeseran struktur perekonomian Kabupaten Majalengka dari sektor pertanian yang dominan tergeser oleh sektor industri pengolahan pada saat pasca pembangunan BIJB Kertajati. Meskipun pada saat ini BIJB Kertajati belum memberikan dampak perekonomian yang signifikan, BIJB Kertajati diproyeksikan akan memberi dampak terhadap perekonomian Kabupaten Majalengka di 20 tahun yang akan datang. Prospek perekmbangan perekonomian juga dapat memanfaatkan realisasi Kertajati Aerocity dan munculnya industri baru di sekitar kawasan BIJB sehingga terciptanya lapangan kerja baru.